Capacity development through training: the case of BRAC village organizations - Mahbub, Sharmin; Mannan, Manzurul; Khan, Shahriar R; Rana, Masud (BRAC Research and Evaluation Division (RED), 2019)
Capacity development through skill training is an important component of BRAC' s credit programme. This study looked at the impact of capacity development of BRAC beneficiaries on their performance as village organization (VO) members as well as use of the skill gained. Qualitative data were collected from 3 VOs of south Uddamdi village of Matlab thana where BRAC started working since early 1992. During analysis comparison was made between members who received training and members who did not receive any training. Results indicate that 27-39% of the VO members chosen for BRAC training were largely selected by VO management committee in consultation with PA and PO. Sometimes a member received training up to 5 times on different topics but did not use more than two. There are large number of non-target group (NTG) members present in these VOs (on average 27%) who influence the selection process. About 83% of the trainees were above the age of 40 years. Also, VO management committee members and small group leaders appeared to be more likely to be selected for training. Statistically significant effect of skill training on savings/credit performance was noted. Group members who received various inputs for capacity development such as training; .credit and employment opportunities were better-off socially and economically than those who did not get this opportunity. While looking for regularity of attendance, it was seen that members who received training were more regular in weekly meetings than those who did not receive any training. Problems in using training knowledge were lack of opportunities and support from fellow group members as well as staff Operational problems associated with training include ,inducing false hope and inadequate supplies of training materials. . Members perception about training was initially not favorable but later when the benefits started showing, their interest increased. The study shows that members perceive the VO as a mechanism through which they may receive services and inputs from BRAC and they exert pressure on BRAC staff to provide ~hem with these inputs. This sometimes stress the relationship between the members and staff. However, VO members and BRAC staff pursue for increased interdependency to, protect the interest of VOs. ·